2019
DOI: 10.1111/ajag.12673
|View full text |Cite
|
Sign up to set email alerts
|

Falls, fear of falling and related factors in community‐dwelling individuals aged 80 and over in Turkey

Abstract: Objective This study aimed to determine the prevalence of falls, fear of falling (FOF) and related factors in individuals aged 80 and over living in the Balçova district of Izmir. Methods One thousand and seventy‐five individuals aged 80 years or older participated. The dependent variables were falls and fear of falling. The independent variables were socio‐demographic and socio‐economic characteristics, health‐related characteristics and 'safety status of home' features. Results The participants’ mean age was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 25 publications
0
13
0
4
Order By: Relevance
“…On the other hand, fear prevalence in our study was substantially lower than the 71% reported in a study of older Turkish patients who underwent total knee or hip replacement (Turhan Damar et al, 2018). The higher prevalence in that study may reflect cultural or demographic differences, or it may reflect the much higher proportion of women in that study (nearly 70%), since older women are more likely to fear falling, based on previous work (Lavedán et al, 2018; Eunmi et al, 2015; Simsek et al, 2020) and the present study.…”
Section: Discussionmentioning
confidence: 55%
“…On the other hand, fear prevalence in our study was substantially lower than the 71% reported in a study of older Turkish patients who underwent total knee or hip replacement (Turhan Damar et al, 2018). The higher prevalence in that study may reflect cultural or demographic differences, or it may reflect the much higher proportion of women in that study (nearly 70%), since older women are more likely to fear falling, based on previous work (Lavedán et al, 2018; Eunmi et al, 2015; Simsek et al, 2020) and the present study.…”
Section: Discussionmentioning
confidence: 55%
“…However, that study may not have evaluated insomnia with an objective method. 46 In the present study, none of the patients used hypnotic drugs, benzodiazepines, non-benzodiazepines, melatonin, or orexin receptor antagonists in the insomnia or control group. Benzodiazepines are the most commonly used drugs for insomnia treatment.…”
Section: Discussionmentioning
confidence: 61%
“…In a study assessing community‐dwelling older people over the age of 80, sleep disturbance was not associated with fear of falling. However, that study may not have evaluated insomnia with an objective method 46 …”
Section: Discussionmentioning
confidence: 99%
“…In total, 1075 elderly participants were evaluated (response rate 67.1%). The data on falls, fear of falls and associated risks have been published from this database elsewhere (14).…”
Section: Methodsmentioning
confidence: 99%